Synthesis of Progressively-Variant Textures on Arbitrary Surfaces - Zhang, Jingdan; Zhou, Kun; Velho, Luiz; Guo, Baining; Shum, Heung-Yeung (ACM Trans. Graph., 2003)
We present an approach for decorating surfaces with progressively variant textures. Unlike a homogeneous texture, a progressively variant texture can model local texture variations, including the scale, orientation, color, and shape variations of texture elements. We describe techniques for modeling progressively-variant textures in 2D as well as for synthesizing them over surfaces. For 2D texture modeling, our feature-based warping technique allows the user to control the shape variations of texture elements, making it possible to capture complex texture variations such as those seen in animal coat patterns. In addition, our feature-based blending technique can create a smooth transition between two given homogeneous textures, with progressive changes of both shapes and colors of texture elements. For synthesizing textures over surfaces, the biggest challenge is that the synthesized texture elements tend to break apart as they progressively vary. To address this issue, we propose an algorithm based on texton masks, which mark most prominent texture elements in the 2D texture sample. By leveraging the power of texton masks, our algorithm can maintain the integrity of the synthesized texture elements on the target surface.